ACUTE FLACCID PARALYSIS SURVEILLANCE: A 5 YEARS STUDY OF BANNU, PAKISTAN - Faheem, Muhamm Umer; Haroon, Muhammad Zeeshan; Khan, Aftab Alam; Shaukat, Maryum; Anwar, Syed Abbas (Journal of Ayub Medical College Abbottabad, 2015)
Background: Acute flaccid paralysis (AFP) is clinical presentation marked by acute onset of weakness and reduced tone. Aetiologies of AFP are diverse including infectious agents, trauma or autoimmune reaction. Currently only three countries in the world that are Nigeria, Pakistan and Afghanistan have endemic poliomyelitis. Pakistan’s polio crisis represents one of the last hurdles in a 23-year campaign run by the World Health Organization. Bannu due to its geographical location stands out to be one of highest risk areas for Poliomyelitis. The objective of this study was to determine frequency of AFP and their aetiologies in District of Bannu during time period of four years from 2007 to 2011. Methods: It was a cross-sectional descriptive study. Data was collected from EDO office District Bannu and analysed using Microsoft Excel 2007. Results: During this period there were 180 cases of AFP in district Bannu. 15% of cases were diagnosed as Guillian Barre Syndrome, making it the leading aetiology. Only 3 (1.66%) cases were diagnosed with Poliomyelitis. Out of 180 AFP cases 104 cases were male and 76 cases were female. Conclusion: Bannu needs enthusiastic educational and vaccination campaigns to eradicate Polio from the area and henceforth from the Pakistan.